TEKNIK PEMBUATAN PUPUK ORGANIK DARI LIMBAH PADAT INDUSTRI MDF - Prabawa, Sigit Baktya (Universitas Nusa Bangsa, 2017)
Â Woody waste from logging activities and the wood processing industry is quite large. If this waste is not utilized, it will cause considerable losses due to wasted woody waste. In Indonesia there are many wood processing industries including the pulp and paper industry, plywood, molding, and medium density fiberboard (MDF). In the MDF industry, chipping are the activities that must be carried out. However, this chipping activity leaves considerable waste in the form of fine chips. Related to this, it is necessary to find and get the use of organic solid waste into a product that can provide added value and technology that can be applied by the communities. One solusion to this is probably by utilizing the waste into organic fertilizer. The aim of this study was to obtain information and technology for making organic fertilizers from the MDF's organic solid waste industry. Fine chip samples were taken from the MDF industry using raw materials from acacia mangium and gmelina, located in Senoni, Kutai Kartanegara Regency, East Kalimantan Province. Organic fertilizer was made by composting using EM-4 microbial consurtium with rice straw and chicken manure additives. The results of the study show that technically the composting of MDF solid waste can be done well. The composting process to mature takes about 4 months. Composting reduces the C element content of MDF waste from around 56% to 25%, and decreases the value of C/N ratio from 347 to around 28. Composting increases the N element more than 5 times, and also increases the content of K elements. Adding rice straw and chicken manure in general it tended to decrease the value of the C/N ratio, increase pH, and increase the levels of elements P, K, Ca and Mg and their cation exchange capacity. The addition of these materials generally made compost meet SNI standards except the compost water content.